A note on a prototype system for simple computer-assisted matching of individually identified southern right whales, Eubalaena australis - Burnell, Stephen R.; Shanahan, David (The journal of cetacean research and management, 2020)
A system using computer assistance in the matching of the callosity patterns of individual southern right whales is described. Whenprovided with a digitised representation of an individual whale’s callosity pattern, the prototype system produces a hierarchical output ofthe most similar patterns in the database with relatively high accuracy. A trial database of binary images of the callosity patterns of 165individually identified southern right whales was created. A further two replicates each of nine different individual whales within the trialdatabase, were then created by two different operators, producing a test set of 18 images. A software program, utilising a pattern recognitionalgorithm and incorporating a mouse driven user interface, was developed so that when provided with a binary bitmap of an individualwhale from the test set, the program compares it against a trial database of previously saved bitmaps and produces a hierarchical outputof the most similar whales, or nearest ‘matches’. For 15 of the 18 test images (83%), the system returned the correct whale as the top matchout of the 165 in the trial database. For the remaining three test images the correct whale was the second, sixth and sixteenth ranked whalein the trial database containing 165 whales. The program was successful in reducing the number of individuals required for manualcomparison to a small percentage of the total catalogue, with a high degree of accuracy, and with a significant associated time saving. Itis envisaged that the final matching will continue to be done visually by an experienced operator using the original photographs. Furtherrefinement of the system with the aim of streamlining and simplifying the input process and incorporating partial pattern recognition isintended.